2005
DOI: 10.3354/dao067015
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of koi herpesvirus infections in common carp Cyprinus carpio

Abstract: Two co-habitation studies with common carp were conducted to determine whether latent infections of koi herpesvirus (KHV) exist. Fish were exposed to KHV using 2 different temperature profiles, which induced low and high initial mortality. Subsequently, certain groups of fish were co-habited with naïve fish while others were not. Koi herpesvirus was reactivated in fish from 3 of the 5 experimental tanks. Reactivation of the virus occurred regardless of the initial mortality associated with the virus or whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(134 citation statements)
references
References 15 publications
5
125
2
2
Order By: Relevance
“…The latency-associated transcript (LAT), which plays a role in inhibiting apoptosis and maintaining latency by promoting the survival of infected neurons, has been detected in HSV-1 (Perng et al 2000). However, few reports have been conducted on latent infection of herpesvirus in aquatic animals, although it has been suggested that carp surviving KHV infection may become a carrier of the virus (St-Hilaire et al 2005, Dishon et al 2007). Currently, we are studying the state of the virus in the main internal organs of carp surviving KHV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The latency-associated transcript (LAT), which plays a role in inhibiting apoptosis and maintaining latency by promoting the survival of infected neurons, has been detected in HSV-1 (Perng et al 2000). However, few reports have been conducted on latent infection of herpesvirus in aquatic animals, although it has been suggested that carp surviving KHV infection may become a carrier of the virus (St-Hilaire et al 2005, Dishon et al 2007). Currently, we are studying the state of the virus in the main internal organs of carp surviving KHV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The best evidence comes from studies of the Lucké tumor, in which RaHV1 nucleic acid and proteins have been demonstrated in non-infectious, virus-free tumor tissue that, upon temperature manipulation, can yield infectious virus (Biggs 1972, Naegele & Granoff 1980, Tweedell 1989. Moreover, evidence for a long-term carrier state, which may or may not involve latency, has been described in several fish HVs, including IcHV1 (Wise et al 1985, Boyle & Blackwell 1991, Baek & Boyle 1996, Gray et al 1999, Thompson et al 2005, SalHV2 (Gou et al 1991, Kimura & Yoshimizu 1998), CyHV1 (Sano et al 1993), AngHV1 (van Nieuwstadt et al 2001, Shih 2004, and CyHV3 (Adkison et al 2005, Bercovier et al 2005, St-Hilaire et al 2005. These reports, and others of an anecdotal nature, indicate the existence of long-term infections (perhaps latency) caused by a wide selection of viruses in the family Alloherpesviridae.…”
Section: Discussionmentioning
confidence: 99%
“…A progressive increase in anti-KHV antibodies in naturally exposed koi is seen by ELISA [69]. These antibodies are detected in the serum at 3 weeks after experimental infection and in survivors after 1 year following a natural infection [1,39,78,81]. KHV infection induces a high prevalence (54 %) of KHV specific antibodies in surviving wild fish population [83]; while studies in farmed fish of England show almost 85-93 % of fish are seropositive by ELISA, even 1 year after disease outbreak [81].…”
Section: Detection Of Khv Antigen/antibodiesmentioning
confidence: 99%
“…In wild populations, KHV can remain as carrier in asymptomatic fish and act as reservoir of infection [83]. Several months after initial exposure to the virus, temperature-dependent reactivation of KHV infection can occur in exposed fish [19,78]. This latency feature of KHV probably contributes in the spread of this pathogen to new geographic locations.…”
Section: Latency In the Hostmentioning
confidence: 99%